2018
DOI: 10.1016/j.ejphar.2018.02.037
|View full text |Cite
|
Sign up to set email alerts
|

The in vitro pharmacology and non-clinical cardiovascular safety studies of a novel 5-HT 4 receptor agonist, DSP-6952

Abstract: The pharmacological activity of DSP-6952, a novel compound was investigated, compared to that of clinically efficacious gastrointestinal (GI) prokinetic 5-hydroxytryptamine (5-HT) receptor agonists. DSP-6952 had a strong affinity of Ki = 51.9 nM for 5-HT receptor, and produced contraction in the isolated guinea pig colon with EC of 271.6 nM and low intrinsic activity of 57%, similar to tegaserod and mosapride. In the development of the 5-HT receptor agonists, cardiovascular risk was deliberately evaluated, bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 52 publications
4
19
0
Order By: Relevance
“…It is also noteworthy that in the present study there were no deaths, cardiovascular toxicity, or abnormal changes in vital signs or 12‐lead electrocardiography. The results of the present study are aligned with those of a preclinical study, which reported that despite a dose‐dependent increase in the heart rate of monkeys treated with DSP‐6952, blood pressure remained normal, and no abnormal electrocardiographic findings, including prolongation of QTc Bazett, were noted . In the same preclinical study DSP‐6952 did not cause coronary artery constriction in rabbits, unlike tegaserod, suggesting that the DSP‐6952 does not induce ischemic heart disease …”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…It is also noteworthy that in the present study there were no deaths, cardiovascular toxicity, or abnormal changes in vital signs or 12‐lead electrocardiography. The results of the present study are aligned with those of a preclinical study, which reported that despite a dose‐dependent increase in the heart rate of monkeys treated with DSP‐6952, blood pressure remained normal, and no abnormal electrocardiographic findings, including prolongation of QTc Bazett, were noted . In the same preclinical study DSP‐6952 did not cause coronary artery constriction in rabbits, unlike tegaserod, suggesting that the DSP‐6952 does not induce ischemic heart disease …”
Section: Discussionsupporting
confidence: 89%
“…The results of the present study are aligned with those of a preclinical study, which reported that despite a dose-dependent increase in the heart rate of monkeys treated with DSP-6952, blood pressure remained normal, and no abnormal electrocardiographic findings, including prolongation of QTc Bazett, were noted. 7 In the same preclinical study DSP-6952 did not cause coronary artery constriction in rabbits, unlike tegaserod, suggesting that the DSP-6952 does not induce ischemic heart disease. 7 Regarding the PK results, after single-dose administration in fasting conditions, the t max of DSP-6952 occurred at 0.5-1 hour after administration, and the t ½ was 7-8 hours.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations